Effectiveness and cost-effectiveness of Chuna manual therapy for temporomandibular disorder: A randomized clinical trial - Jae-Heung Cho; Koh-Woon Kim; Hyungsuk Kim; Woo-Chul Shin; Me-riong Kim; Joowon Kim; Min-Young Kim; Hyun-Woo Cho; In-Hyuk Ha; Yoon Jae Lee (PLoS ONE, 2025)
The effectiveness and cost-effectiveness of Chuna manual therapy (CMT) for temporomandibular joint disorders (TMD) remain unclear. Here, we compared the effectiveness of CMT and usual care for treating myofascial TMD. A 26-week randomized controlled trial was conducted from 2018 to 2019 with 80 patients across five hospitals in Korea who were diagnosed with myofascial TMD and had temporomandibular joint (TMJ) pain lasting more than three months. Patients were randomly assigned in a 1:1 ratio to either the CMT group, which underwent eight sessions of CMT over four weeks, or the usual care (UC) group, which received physical therapy for the same period. Treatment effectiveness was evaluated in terms of pain, function, and quality of life over 26 weeks. For determining cost-effectiveness, quality-adjusted life years (QALY) were analyzed, and the incremental cost-effectiveness ratios from the societal and healthcare system perspectives were calculated. At week 5, the visual analog scale (VAS) scores decreased more in the CMT group than in the control group, although the difference was statistically insignificant. The CMT group showed significant improvement in specific functional and quality of life measures, particularly in the EuroQoL-VAS (-13.21 (95% confidence interval [CI] -20.03 to -6.38) and the Jaw Functional Limitation Scale-Global score of 0.59 (95% CI 0.13 to 1.05), through improvements were not consistent across all indices. The CMT group showed a slightly higher QALY, and the 26-week incremental cost in the CMT group was $338 lower than that of the usual care group. The cost of CMT was $150 higher than that of usual care, and the incremental cost-effectiveness ratio per utility ranged from $4,011 to $17,851. When a “willingness to pay for treatment ($26,375)” threshold was applied, the probability of CMT being cost-effective was 68.1%–98.3%. Despite no significant differences in pain reduction at week 5, CMT was found to be a cost-effective treatment for TMD, particularly for improving function and quality of life. These findings may serve as a basis for considering the expansion of national health insurance coverage for Chuna therapy in Korea. Trial Registration: Clinical Research Information Service KCT0003192